Study on the Physical Characteristics of Plasma and Its Relationship with Pore Formation during Laser-Metal Active Gas Arc Hybrid Welding of 42CrMo Steel - Yan Zhang; Hao Li; Xin Mi; Hongzhi Zhou; Mingjun Zhang; Zhongmin Wan; Liyuan Tang (Photonics, 2023)
The automobile industry puts forward higher requirements for the design and manufacture of steel pistons. However, the welding of 42CrMo steel pistons still has unsolved technical problems, especially welding defects that cannot be directly detected, such as pores, which are easily generated inside the weld. A plasma experiment of laser-metal active gas arc (MAG) hybrid welding 42CrMo steel was conducted in this paper, and plasma signals inside and outside the keyhole were detected during the laser welding, leading laser laser-MAG hybrid welding, and leading arc laser-MAG hybrid welding of 42CrMo steel. The characteristic parameters such as electron temperature and electron density were calculated and analyzed to investigate the relationship between plasma behavior and the formation of weld porosity in the welding process of 42CrMo steel. Based on the fluctuations in plasma electron temperature and electron density, the prediction of pore formation in the weld of 42CrMo steel was made, aiming to provide guidance for achieving a stable and reliable laser-MAG hybrid welding process for 42CrMo steel.